2021
DOI: 10.1155/2021/5539544
|View full text |Cite
|
Sign up to set email alerts
|

Efforts Made to Eliminate Drug‐Resistant Malaria and Its Challenges

Abstract: Since 2000, a good deal of progress has been made in malaria control. However, there is still an unacceptably high burden of the disease and numerous challenges limiting advancement towards its elimination and ultimate eradication. Among the challenges is the antimalarial drug resistance, which has been documented for almost all antimalarial drugs in current use. As a result, the malaria research community is working on the modification of existing treatments as well as the discovery and development of new dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 101 publications
0
16
0
1
Order By: Relevance
“…For lack of means, some resort to traditional medicine in the event of malaria using an infusion or a decoction based on the bark of Quinquina (Cinchona officinalis). Plasmodium falciparum develops resistance to several drugs globally, so its resistance only targets quinine and Artemisinin derivatives (the most widely used antimalarials in our region) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For lack of means, some resort to traditional medicine in the event of malaria using an infusion or a decoction based on the bark of Quinquina (Cinchona officinalis). Plasmodium falciparum develops resistance to several drugs globally, so its resistance only targets quinine and Artemisinin derivatives (the most widely used antimalarials in our region) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies indicated that self-medication is associated with inappropriate treatments and polychemotherapy [ 12 , 13 ]). In Bukavu, a town in the eastern region of the DRC, and elsewhere in the country, there are no regulations on the sale and use of pharmaceuticals, which then results in a high incidence of self-medication of Antimalarial drugs [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…To prevent the development of parasite resistance, therapeutic management with drugs that inhibit the major pathogens is required. In the case of cytochrome bc 1 inhibitors, new antimicrobial agents are being explored primarily with this goal in mind [ 66 , 67 ]. DQ has previously been described as a drug that exhibits cross-resistance.…”
Section: Pharmacological Usementioning
confidence: 99%
“…It should be clarified that DQ has limited cross-resistance to atovaquone-resistant parasites, with mutations A122T and Y126C at the cytochrome b binding site. However, one mutation that occurs in atovaquone is Y268S, which leads to late treatment failure [ 66 ]. Another mutation that leads to atovaquone resistance and corresponds to one of the most common mutations in P. falciparum is Y279S, which led to the reversal of the DQ snapping position.…”
Section: Pharmacological Usementioning
confidence: 99%
See 1 more Smart Citation